Analysis of Occupational Health and Safety Programs to Reduce Work-place Accidents in Nickel Mining Areas - Wimar Muhammad; Agus Hermawan; Naswan Suharsono (Master of Management FEB ULM, 2026)
This study was motivated by the high-risk nature of mining operations and the need to ensure worker safety at PT Vale Indonesia Tbk’s nickel mining site in Sorowako. The objective was to assess the implementation and effectiveness of its Occupational Health and Safety (OHS) program, particularly in preventing workplace accidents. A qualitative phenomenological approach was employed, involving in-depth interviews with six key informants. The findings indicate that the OHS program has contributed to a notable decline in minor accidents between 2022 and 2023, largely due to safety education, consistent enforcement of procedures, and regular safety communication. Nevertheless, challenges remain—such as uneven implementation, limited employee engagement, and the prevalence of unsafe behaviors, which account for the majority of incidents. The study concludes that achieving a truly effective safety culture requires moving beyond compliance toward shared responsibility, supported by strong leadership, active workforce participation, and the adoption of innovative tools and global best practices to realize the company’s zero-harm vision.Practically, these findings offer an evidence-based roadmap for strengthening OHS systems in dynamic nickel mining environments; theoretically, this study enriches phenomenological discourse on the interplay between safety policies, human behavior, and technology within extractive industries in Indonesia.